The anxiety, depression, and TMD: Multidisciplinary therapy - Prada, Simone Graziani; Siqueira , Adriana Ugolini Benatti de; Camargo , Gabriela Machado; Roesler, Célia; Silva , Evelyn Esteves de Oliveira; Couto Junior, Oswaldo; Saba , Felipe Sampaio; Moura , Raphael Zanetti Sarra; Nobre , Shinji Yamashita; Zanetti , Claudia (Headache Medicine, 2024)
Abstract Introduction Temporomandibular disorder (TMD) affects the jaw and muscles, often linked to stress, anxiety, and sleep issues. Comprehensive care addressing physical and psychological factors improves outcomes. Objective This study proposed a multidisciplinary approach (psychologists, dentists, and physical therapists) to treat these conditions with non-pharmacological techniques, aiming for a more effective and personalized treatment. Method The research was conducted at the Sacomã Basic Health Unit in São Paulo, Brazil, and included 12 healthcare professionals in an active intervention and 6 patients as a control group during 1 month. The intervention consisted of four weekly one-hour sessions and home therapies sent via WhatsApp, utilizing stretching, mindfulness, thermotherapy, self-massage, and cognitive-behavioral therapy. Participants completed pre- and post-intervention questionnaires on depression (PHQ-9), anxiety (GAD-7), bruxism (OBC), and pain (GCPS and Pain Drawing). Results The interventions resulted in significant reductions in the PHQ-9 (p=0.028), GAD-7 (p=0.039), OBC (p=0.015), and PD (p=0.016) scales, demonstrating the positive impact of group dynamics. Additionally, there was a decrease in pain and an improvement in the quality of life of the participants. Conclusion Despite sample limitations, the data indicate that multidisciplinary interventions can effectively manage TMD, resulting in reduced pain and associated symptoms. The approach showed potential to improve patients’ quality of life, highlighting the importance of integrated and personalized treatment. Future studies with larger samples and extended follow-up are necessary to validate these findings and expand the applicability of the